Minimasi Biaya Produksi Roda Karet R 300 Dengan Metode Forecasting dan Agregat Planning Pada Cv Baja Makmur 2 - Dimas Ihza Mahendra; Widya Setiafindari (Pusat Riset dan Inovasi Nasional, 2023)
CV Baja Makmur 2 is a company engaged in metal casting, one of the products produced by the company is a rubber wheel product where rubber wheel products have several types including R 100, R150, R 300, R 500, R750, and R 1000. In wheel production R 300 rubber found a problem where the average level of production was around 979 pcs higher compared to the average demand of only 940 pcs, this could cause an increase in production costs incurred by the company. The purpose of this research is to minimize the production cost of R 300 rubber wheels for the next 12 months, using the Forecasting method to predict the number of requests and Aggregate Planning to minimize production costs. The results of this study indicate that the Forecasting method using ARIMA obtained the best model (0,1,1) with an MSE value of 40969.4. In the Aggregate Planning method using the Level Method the minimum production cost for the next 12 periods is around Rp 258.802.500.